SISTEM INFORMASI ADMINISTRASI OPERASIONAL VENDOR ATM PADA PT WIRATANU PERSADA TAMA CABANG MALANG - Fajar Lailatul Masruroh; Dian Wahyuningsih (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2023)
PT Wiratanu Persada Tama Branch Malang certainly has a close relationship with the storage of data every day (especially the administration section) including employee data, client data, the data of ATM, the data transactions, charging money, traffic data maintenance etc. But in fact the reports presented are still common flaws - flaws include data redundancy, inefficient processing time, the search data is still manual and each month must re-create the formula - the formula manually to manipulate all of the data is done With the processing system inadequate and also driven by an increase in managed ATM entrusted to the company (the client).The use of systems development methods, can provide a solution to the system running is using SDLC (System Development Life Cycle). Results of research conducted resulted that the proposed system can help the performance of the administration of PT Wiratanu Persada Tama Branch Malang as evidenced by the efficiency of processing time reports using the old system takes 1 day to print monthly statements while using this information system takes less less than 10 minutes.